A white feathered area on the forehead is more common in hybrids of Greylag Goose Anser anser and Greater Canada Goose Branta canadensis than in the parent species - Gustavsson, C G (Ornis Svecica, 2011)
This study evaluated prevalence and extent of white areas on heads of Greylag Goose × Greater Canada Goose hybrids. A white area which bordered the bill and then to various degrees extended over the forehead was found in 17 out of 20 hybrids. This was significantly more common in the hybrids than in the parent species. The white areas in the hybrids were also significantly larger than in those 82 out of 191 adult Greylag Geese which had some amount of white area. There were too few Greater Canada Geese with a white area outside the normal pale cheek patch to make a meaningful similar quantitative comparison also with them. No white area was seen in the three presumed 1st Calendar Year (CY) hybrids but when two of them were seen again in September of the 2nd CY there were some pale feathers that were interpreted as the beginning of white areas. The white areas in hybrids are therefore regarded to be adult features which like in several pure Anser species begin to develop during the 2nd CY.